Sigma 7 The Six Mercury Orbits of Walter M. Schirra, Jr. - Burgess, Colin (Space Exploration, 2016)
Colin Burgess offers a comprehensive yet personal look at the 1962 orbital mission of Wally Schirra aboard the spacecraft Sigma 7, the first book about this popular pioneering astronaut which explores his entire life and accomplishments. This continues the author's attempt to fully document the record of Project Mercury's pioneering early phase of the Space Age. Schirra's pre-NASA life is examined, as well as his training as a NASA astronaut and for his Mercury MA-8 flight. The 6-orbit flight of Sigma 7 is fully covered from its origins through to the spacecraft's safe recovery from the ocean after a highly successful Mercury mission. Schirra's participation on the Gemini 6 and Apollo 7 missions is also told, but in brief, and the book also relates his post-NASA life and activities through to his passing in 2007. The Mercury Seven occupy a unique spot in the history of human spaceflight, and Schirra is at last given his due as one of the contributing astronauts in this painstakingly researched book.